Inclusivity and Deradicalization of Religion - muhammad Hifdil Islam (Institut Ilmu Keislaman Zainul Hasan Genggong, 2016)
Claims of absoluteness for each religion being enlarged by thedifferences between religions. Inclusive problem in Islam is a continuationof the thought or the idea of neo-modernism to a more specific area afterpluralism, precisely in the field of theologywithout leaving a space oftolerance in this field. For empathy or sympathy, how others perceive theirown religion and we often judge the faith of others by seeing our owntheology. To solve that we can use an external relations for the creation ofreligions, interreligious dialogue needs to be done. Then, in the internalreligion,it is required a reinterpretation of religious messages moreuniversal human touch. Problem formulation problems associated withit can be taken the following issue of religious inclusiveness relationshipwith the efforts of inter-religious harmony.